Trade liberalisation does not contribute to food security! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
This publication reports on eight case studies that illustrate the impact of agricultural trade and structural adjustment on people in developing countries. From Benin through India to the Philippines, they show that 'exporters have gained, but the...